His accidental Amish family - Good, Rachel J. (Good, Rachel J. Unexpected Amish blessings., 2020)
After a buggy accident when she was a teenager, Anna Flaud was told she would never walk again. Unwilling to be an object of pity, she put aside her dreams of marriage and found purpose as an assistant at a Community Care Center. Now she has a chance to fulfill her dearest wish, motherhood, and adopt three siblings with special needs. Yet the opportunity comes with a condition Anna isn't sure she can meet: finding a husband. Levi King began working at the center as penance after a careless mistake led to tragedy. Though he's dealing with his own heartbreak, he's drawn to Anna, cheering her on as she strives to regain her mobility. Her quiet determination, her generous heart, these are qualities to cherish in a wife.